Association between Body Image and Self Esteem Among Senior High School Female Students - Michael; Prihadi; Dharmady Agus (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Introduction. Many teenagers experience dissatisfaction with changes in body shape. Mismatched the reality of actual body shape and ideal body image perception triggers negative body image perception, which can cause a decrease in selfesteem. In terms of gender, women's self-esteem levels tend to be lower compared to men. Methods. This study was an observational analytic study with a cross-sectional approach, taken at Fons Vitae I Senior High School with stratified random sampling. The body image was measured by using Body Shape Questionnaire-34 (BSQ-34), and self-esteem was measured by using the Rosenberg Self Esteem Scale (RSES) questionnaire. Data are analyzed using chi-square. Results. The total respondents were 109 female students. In univariate analysis, there were 13.8% female students who had dissatisfaction with her body image and 86.2% female students who had satisfaction with her body image. Female students with low self-esteem were 19.3%, and high self-esteem was 80.7%. The bivariate analysis shows that there is a significant association between body image and the level of self-esteem among Senior High School female students (p = 0.039) with OR = 3.511. Conclusion. There is a significant association between body image and level of self-esteem.